Strategies of Legitimization through Axiological Proximization in War Poetry - Khan, Faisal; Haidar, Sham; Masroor, Farzana (Pakistan Journal of Humanities and Social Sciences, 2023)
Despite an increased interest in war studies and militant discourse in recent years, proximization and legitimization perspectives remain scarce. This paper investigates such perspectives in war poetry by proposing a framework of axiological proximization. In this paper, we have focused upon axiological proximization that is a forced construal of a mounting ideological conflict between the political speaker and his/her enemy. This paper focuses on rhetoric of war poetry from Afghanistan and Kashmir concerning legitimization strategies. The study is qualitative in nature and lays emphasis upon the ways war poetry as a critical language embarks upon proximization and legitimization strategies especially via axiological proximization. The movement from ideological clash to the physical conflict is an essential part of axiological conflict. Axiological proximization marks the “self” with positive home-values and the “other” with alien values. This leads to antagonism between the ‘home values’ of the political speaker and ‘alien values’ of the enemy. The mechanism of axiological proximization is a salient feature of rhetoric of war poetry from Afghanistan and Kashmir where the two antagonistic ideologies are contrasted: freedom of the East versus negative values of the West.